Peran Komunikasi Bahasa Ibu dan Literasi Kesehatan dalam Pencegahan Stunting pada Anak Usia Dini bagi Warga Binaan di Rumah Tahanan Negara (Rutan) Kelas II B Sibuhuan - Purba, Happy Sri Rezeki; Lubis, Ainun Mardiyah; Padly, Fajar; Saifuddin, Bandaharo; Busyro, Marwan; Lubis, Laila Tussifah; Humala, Fahmi; Sembiring, Anastasia Leonita (Jurnal Bahastra, 2025)
This study aims to analyze the role of mother-tongue-based communication and health literacy in preventing stunting among early childhood children of inmates at Class II B Correctional Facility Sibuhuan. The research employed a quasi-experimental design using a one-group pre-test and post-test model. A total of 40 inmates participated as respondents and received health education interventions delivered in their native language. Data were collected through health literacy questionnaires, knowledge tests, in-depth interviews, and participatory observation. The results revealed a significant increase in health literacy scores (from 52.3 to 78.6) and knowledge regarding stunting prevention (from 34.3% to 79.5%) after the intervention. Regression analysis showed that health literacy had a significant influence on knowledge improvement (R² = 0.642; p < 0.05). These findings demonstrate that communication using the mother tongue effectively enhances inmates’ understanding and participation in health education programs. The study recommends implementing a mother-tongue-based health education model as an effective strategy for stunting prevention, particularly in vulnerable and marginalized communities.